IMPLEMENTASI METODE DISKUSI DAN PENUGASAN DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VII DI UPT SPF SMP NEGERI 40 MAKASSAR - Ridhotul Mubaraq R (CV. Adiba Aisha Amira, 2024)
This research is classroom action research which aims to determine the increase in the use of Discussion and Assignment learning methods to improve Civics learning outcomes, Lesson 2023/2024. The subjects of this research were 33 students in class VII.6 UPT SPF SMPN 40 MAKASSAR. This research was carried out in three cycles with each cycle having four stages, namely planning, implementation and observation, and reflection. This Classroom Action Research (PTK) aims to find out whether the use of Discussion and Assignment learning methods can improve student learning outcomes. The aim of the researcher in carrying out PTK using the Discussion and Assignment learning method in Civics learning is to find out whether the application of the discussion and Assignment method can improve student learning achievement. Based on the research that has been carried out, the results of cycle I showed that the percentage of student activity was 60.75% and the average value of the new class reached the average value of the class (67.19) and the classical learning completeness value (53.13%). Meanwhile, in cycle III, the percentage of student activity was 78.085% with a very good category and the class average score was (75.94) and the classical learning completeness score was (87.50%). Thus it can be concluded that the application of the Discussion and Assignment learning method to improve Civics learning outcomes is able to increase student activity and is able to improve student learning outcomes in Class VII.6 UPT SPF SMPN 40 MAKASSAR Academic Year 2023/2024. Thus, the use of image media in learning can increase teacher activity, student activity and student learning outcomes so that the quality of learning increases.